The phenotypic and genetic spectrum of patients with heterozygous mutations in cyclin M2 (CNNM2) - Franken, Gijs A. C.; Müller, Dominik; Mignot, Cyril; Keren, Boris; Lévy, Jonathan; Tabet, Anne‐Claude; Germanaud, David; Tejada, María‐Isabel; Kroes, Hester Y.; Nievelstein, Rutger A. J.; Brimble, Elise; Ruzhnikov, Maria; et al. (Human mutation, 2021)
Hypomagnesemia, seizures, and intellectual disability (HSMR) syndrome is a rare disorder caused by mutations in the cyclin M2 (CNNM2) gene. Due to the limited number of cases, extensive phenotype analyses of these patients have not been performed, hindering early recognition of patients. In this study, we established the largest cohort of HSMR to date, aiming to improve recognition and diagnosis of this complex disorder. Eleven novel variants in CNNM2 were identified in nine single sporadic cases and in two families with suspected HSMR syndrome. 25Mg2+ uptake assays demonstrated loss‐of‐function in seven out of nine variants in CNNM2. Interestingly, the pathogenic mutations resulted in decreased plasma membrane expression. The phenotype of those affected by pathogenic CNNM2 mutations was compared with five previously reported cases of HSMR. All patients suffered from hypomagnesemia (0.44–0.72 mmol/L), which could not be fully corrected by Mg2+ supplementation. The majority of patients (77%) experienced generalized seizures and exhibited mild to moderate intellectual disability and speech delay. Moreover, severe obesity was present in most patients (89%). Our data establish hypomagnesemia, seizures, intellectual disability, and obesity as hallmarks of HSMR syndrome. The assessment of these major features offers a straightforward tool for the clinical diagnosis of HSMR. Eleven novel variants in CNNM2 were identified in nine single sporadic cases and in two families with hypomagnesemia. Our data establish hypomagnesemia, seizures, intellectual disability, and obesity as hallmarks of HSMR syndrome, caused by CNNM2 mutations